Impact of Leadership Style, Work Motivation, Organization Culture Toward Satuan Polisi Pamong Praja Work Performance - Astuti, Rulyta Yuli; Sa'adah, Noor; Rahmawati, Salis Diah; Astuti, Jannah Puji; Suprapti, Suprapti; Sudargini, Yuli (Journal of Industrial Engineering & Management Research, 2020)
The aim of this study is to analyze the effect leadership style, work motivation and organization culture toward Satuan Polisi Pamong Praja work performance. The method used in this study is quantitative method. Data was collected by distributing questionnaires to 85 respondents of Satuan Polisi Pamong Praja in Semarang Central Java . For questions about the identity of respondents designed in the form of a semi-open questionnaire in addition to a closed questionnaire. Data collection technique is using questionnaire with Likert Scale. Analysis from this study is SEM (Structural Equation Model) with SmartPLS version 3.0 as a statistic tools. Based on the results of data analysis through a questionnaire distributed to respondents, found several conclusions , There is a significant effect of leadership style on work Performance. There is a significant effect of motivation on work Performance and There is a significant effect of organization culture on work Performance.